2018
DOI: 10.9734/ijpss/2018/42796
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Evaluation of Antioxidant, Antibacterial and Cytotoxicity Activities of Methanolic and Ethanolic Extracts of Enhydra fluctuans Lour (Helencha) (Family: Asteraceae) Stems and Leaves

Abstract: Aims: To investigate the presence of various phytochemicals and to evaluate DPPH scavenging activity, total flavonoid content, antimicrobial and cytotoxic activities of the different extracts of Enhydra fluctuans lour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Kuri et al [16] showed the presence of flavonoids, saponins, diterpenes, triterpenes and phenols, in methanolic extracts of E. fluctuans, and, similar to the instant study, cardiac glycoside was not detected. Haoya et al [17] reported the presence of steroids, saponins, flavonoids and diterpenes, both in methanolic and ethanolic extracts of E. fluctuans, displaying antibacterial activity against E. coli (ZDI: 12 mm at 400 µg/disc) with the ethanolic extract. As per the report of Sarma et al [13], the E. fluctuans toluene and methanol extracts contained bioactive compounds (saponins, tannins, alkaloids, flavonoids, anthraquinones, cardiac glycosides and steroids) showing a broad spectrum of antibacterial activity.…”
Section: Figure 1 Mic (Minimum Inhibitory Concentration) Values Of Methanolic Extract Of E Fluctuansmentioning
confidence: 99%
“…Kuri et al [16] showed the presence of flavonoids, saponins, diterpenes, triterpenes and phenols, in methanolic extracts of E. fluctuans, and, similar to the instant study, cardiac glycoside was not detected. Haoya et al [17] reported the presence of steroids, saponins, flavonoids and diterpenes, both in methanolic and ethanolic extracts of E. fluctuans, displaying antibacterial activity against E. coli (ZDI: 12 mm at 400 µg/disc) with the ethanolic extract. As per the report of Sarma et al [13], the E. fluctuans toluene and methanol extracts contained bioactive compounds (saponins, tannins, alkaloids, flavonoids, anthraquinones, cardiac glycosides and steroids) showing a broad spectrum of antibacterial activity.…”
Section: Figure 1 Mic (Minimum Inhibitory Concentration) Values Of Methanolic Extract Of E Fluctuansmentioning
confidence: 99%